Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT Pardasyi Cahaya Abadi Jakarta - Rahman Nur Fahri; Lukman Hakim (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The purpose of this study is to find out and analyze the influence of the work environment and work discipline on the performance of PT Pardasyi Cahaya Abadi employees partially and simultaneously. The research method used in this study is a quantitative method. The population in this study is all employees of PT Pardasyi Cahaya Abadi. The sample in this study uses the entire population as a sample of 38 employees of PT Pardasyi Cahaya Abadi. The data collection techniques in this study use interview, observation, and questionnaire techniques. The data analysis technique in this study uses the Instrument Test, the Classical Assumption Test, the Hypothesis Test using the Multiple Linear Regression Analysis Test and the Determination Coefficient Test (R2). Data processing in this study uses the SPSS software program version 27. The results of this study prove that partially the work environment has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, and simultaneously the work environment and work discipline have a positive and significant effect on the performance of PT Pardasyi Cahaya Abadi employees